Development of high spatial resolution rainfall climatology for Ghana - Aryee, Jeffrey (2016)
A thesis submitted to the Deparment of Physics, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the degree of Master of Philosophy (Meteorology and Climate Science).